To Block Spam, Demand Sender Authentication. - Matioc, Marius; Bellovin, Steven M.; Hubert, Richard; Wolfe Jr., Andrew D.; Foulser, David; Kilner, Andrew R. (Communications of the ACM, 2005)
Presents several letters to the editor. Use of authentication for protecting email from spam; Response to the article "Practical Programmers," by L. Glass, published in the November 2004 issue of the journal "Communications of the ACM"; Information on the skill set of Java programmers.